Penerapan Model Pembelajaran Berbasis Riset pada Mata Kuliah Ekonomi Mikro dalam Meningkatkan Kemampuan Berfikir Kristis Mahasiswa - Forijati Forijati (International Consortium of Education and Culture Research Studies, 2019)
Micro economy subject is planned to facilitate students with the basic comprehension about scope, problems and the basic concepts of economy. In addition, good understanding and critical thinking about microeconomics is very important for managerial decision making processes, understanding the public policy and knowing the way how modern economy runs. The purpose of this study was to find out how the application of research-based learning models in Microeconomics courses to improve students' critical thinking skills. This study uses a type of lesson study based classroom action research with a qualitative descriptive research approach. The research procedure consists of three cycles in which in each cycles there was one topic to know the result that could be achieved by the research subject as the basis for the improvement in the next cycle. Every cycles consist of three steps; Plan, Do and See.The subject of this research was the students of Economy Education Department who were taking micro economy subject. From the results of the study it can be explained that in the first cycle the average implementation of learning was 2.80 (good enough) and the second and third cycles were 3.20 (good enough) and 3.58 (good) respectively. So it can be concluded that there is an increase in Microeconomics critical thinking skills per cycle by using a research-based learning model.